Urban and rural development in Nigeria - Ajaegbu, Hyacinth I. (London : Heinemann Educational, 1976)
This study tries to identify the areas which could be mobilized for accelerated growth and regional development. It tries also to determine the best organization for the space-economy, and the right inputs of development impulses and projects that would make for spatial interlinkages and mutual functional interactions between locations, areas and peoples, in order to enhance national growth and regional development equity.
Includes bibliographical references and index.
ne 05/08/2021
Loans
Keywords: Regional planning; Urbanization; Nigeria